Synthesis and Antifungal Activity of Some 3-[3-(5-Nitro)indolyl]-5-(4-substituted phenyl)isoxazoline and Isothiazoline Derivatives - Kumar Ahirwar, Mukesh; Bardia, Rahul; Shrivastava, S.P. (Asian Journal of Chemistry, 2010)
1-[3-(-5-nitro)indolyl]-3-substituted phenyl-2-ene-propanones 3(a-i) were react with ethanol, hydroxylamine hydrochloride and aqueous NaOH to give 3-[3-(5-nitro)indolyl]-5-substituted phenyl isoxazolines 4(a-i). Isoxazolines 4(a-i) was refluxed with phosphorous pentasulphide in pyridine to give 3-[3-(5-nitro)indolyl]-5-substituted phenyl isothiazolines 5(a-i). All the synthesized isoxazoline and isothiazoline were screened for antifungal activity.